Grande enciclopédia Portuguesa e Brasileira - dir. Francisco de Paula Leite Pinto (Editorial Enciclopédia, 1981)
1.º vol.: A - AZUR, 766 p.; 2.º vol.: BAAD - CARM, 604 p.; 3.º vol.: CARM - CZES, 608 p.; 4.º vol.: D - EYSE, 591 p.; 5.º vol.: F - GYOR, 638 p.; 6.º vol.: H - KYUS, 587 p.; 7.º vol.: L - METE, 593 p.; 8.º vol.: METE - OZU, 591 p.; 9.º vol.: P - QUOC, 592 p.; 10.º vol.: R - ZUZA, 599 p.